2015
DOI: 10.1007/s10886-015-0586-6
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Defense Chemicals in Milkweed Reduce Parasite Infection in Monarch Butterflies, Danaus plexippus

Abstract: In tri-trophic systems, herbivores may benefit from their host plants in fighting parasitic infections. Plants can provide parasite resistance in two contrasting ways: either directly, by interfering with the parasite, or indirectly, by increasing herbivore immunity or health. In monarch butterflies, the larval diet of milkweed strongly influences the fitness of a common protozoan parasite. Toxic secondary plant chemicals known as cardenolides correlate strongly with parasite resistance of the host, with great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 11 publications
0
51
0
Order By: Relevance
“…On A. syriaca, a plant with low cardenolide content, larvae protected in cages had a higher survival rate (92%) than larvae left free on plants (24%) (Zalucki et al 2001b). Adding cardenolides to the artificial diet fed to monarch caterpillars infected with O. elektroscirrha slowed parasite growth and increased lifespan of infected but not uninfected butterflies (Gowler et al 2015). Cardenolide consumption thus appears to mediate a trade-off between toxicity and protection.…”
Section: Monarch Butterflymentioning
confidence: 97%
“…On A. syriaca, a plant with low cardenolide content, larvae protected in cages had a higher survival rate (92%) than larvae left free on plants (24%) (Zalucki et al 2001b). Adding cardenolides to the artificial diet fed to monarch caterpillars infected with O. elektroscirrha slowed parasite growth and increased lifespan of infected but not uninfected butterflies (Gowler et al 2015). Cardenolide consumption thus appears to mediate a trade-off between toxicity and protection.…”
Section: Monarch Butterflymentioning
confidence: 97%
“…Previous studies have shown that infected monarchs reared on milkweeds with high cardenolide concentrations exhibit reduced parasite loads and increased tolerance to parasites (de Roode et al, 2008a(de Roode et al, , 2011aLef`evre et al, 2010;Sternberg et al, 2012;Gowler et al, 2015;Tao et al, 2015Tao et al, , 2016. Cardenolides may cause these reductions in parasite loads by increasing host immunity to the parasite, as has been seen in other systems (Lee et al, 2008;Povey et al, 2009;Simpson et al, 2015), or by direct inhibition of parasites (Cory and Hoover, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Many previous studies have documented the antimicrobial, antiviral, anti-parasitic, and anti-cancer qualities of plant secondary chemicals (Ohigashi et al, 1992;Murakami et al, 1994Murakami et al, , 1996Billing and Sherman, 1998;Sherman and Billing, 1999). In the monarch-parasite system, infected monarch butterflies have shown decreases in parasite loads and increases in tolerance to O. elektroscirrha when reared on milkweeds with higher cardenolide concentrations (de Roode et al, 2008a(de Roode et al, , 2011bSternberg et al, 2012;Gowler et al, 2015;Tao et al, 2015Tao et al, , 2016. Although the medicinal qualities of numerous plant chemicals are clear (Hunter, 2016), their direct effects on parasite morphology, as well as any related effects on pathogenicity and transmission, are unknown (Okagaki et al, 2010;Zaragoza et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of cardenolides in milkweed species could lower O. elektroscirrha infestation. For instance, monarch larvae reared on A. tuberosa, feeding on higher doses of cardenolides resulted in lower parasite infestation of their pupae (Gowler et al, 2015).…”
Section: Natural Enemies: Role Of Pests Pathogens and Diseasesmentioning
confidence: 99%